Improving duration of kangaroo mother care by using quality improvement methodology of low-birth-weight neonates - Mehta, Anita; Kumari, Smriti; Shankar, Vijay (International Journal of Contemporary Pediatrics, 2025)
Background: Kangaroo mother care (KMC) is an evidence-based neonatal care that resulted in decreased mortality and morbidity in preterm infants. The objective of this study was to improve the duration of KMC for Low Birth Weight (LBW) neonates using a Quality Improvement (QI) methodology. Methods: This hospital-based study was carried out among eligible low birth weight neonate-mother dyad at the Neonatal Unit of Baba Raghav Das Medical College, Gorakhpur, Uttar Pradesh, India. Quality Improvement methodology was used, which included counseling and sensitization of staff nurse and family members about KMC, reward and positive reinforcement of staff nurse and family members and implementation of a written hospital policy. The effect of KMC was assessed by duration of KMC in three Plan-do-study-act (PDSA) cycles, each of 3 months duration. Data was analyzed by using SPSS. Results: The total duration of KMC was increased from 6.28 hours/day during PDSA-1cycle to12.13 hours/day during PDSA-3 cycle. Conclusions: By applying QI methodology with existing infrastructure and staff only, there was improvement in KMC duration in preterm LBW neonates.